2022
DOI: 10.3390/children9121923
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in Children with SARS-CoV-2 Infection: Epidemiological, Clinical and Neurophysiological Characterization

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may present with a wide variety of symptoms, including neurological manifestations. We investigated clinical, demographic, laboratory, neurophysiological and imaging characteristics of SARS-CoV-2-positive children with seizures and analyzed differences between children admitted during the periods with prevalent circulation of the Alpha/Delta and Omicron variants, respectively. Patients’ characteristics were analyzed according to the presence or absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
3
11
1
Order By: Relevance
“… 5 6 8 Our finding of an increased prevalence of seizures in patients with SARS-CoV-2 during the omicron period is in line with other currently available studies. 8–10 We additionally showed that SARS-CoV-2 was related to significantly increased rate of seizures in the absence of fever and age >5 years compared with other RTIs, which suggests a more complex pathogenesis of seizures due to SARS-CoV-2 as compared with febrile seizures in children younger than 5 years old. 17 …”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“… 5 6 8 Our finding of an increased prevalence of seizures in patients with SARS-CoV-2 during the omicron period is in line with other currently available studies. 8–10 We additionally showed that SARS-CoV-2 was related to significantly increased rate of seizures in the absence of fever and age >5 years compared with other RTIs, which suggests a more complex pathogenesis of seizures due to SARS-CoV-2 as compared with febrile seizures in children younger than 5 years old. 17 …”
Section: Discussionmentioning
confidence: 58%
“…It is currently unclear if SARS-CoV-2 and especially the omicron variant is more neurotropic compared with other viruses, or if the increased incidence of seizures in patients with SARS-CoV-2 during the omicron period is multifactorial with involvement of more epidemiological factors. 8 Our findings indicate that the omicron variant of SARS-CoV-2 may be more neurotropic than other viruses affecting the respiratory system. However, more data are warranted in order to understand if the omicron variant implicates seizures through enhanced activation of inflammatory response or through affecting more individuals because of its higher contagiousness resulting to more total admissions due to seizures, even if the overall prevalence of seizures in patients with SARS-CoV-2 per se would not be affected, at least during the study period.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…With the gradual mutation of SARS-CoV-2, the Omicron variant dominates worldwide [2]. Recent studies have found an increase in the frequency of seizures in children during the Omicron epidemic [3][4]. In addition, a recent study reported severe neurological disease in several SARS-CoV-2 infected children with fever and seizures as the main clinical manifestations [5].However, the current studies on COVID-19 and seizures are few and mostly in febrile convulsions.Therefore, this study will not be limited to febrile seizures(FS), but will include patients who present with fever and seizures.This study will summarize the clinical features and severity of seizures in febrile children with SARS-CoV-2 infection, analysis of risk factors for recurrent seizures within a short period of time in children with SARS-CoV-2 infected febrile convulsions, and provide a detailed description of children with secondary severe neurological disease.…”
Section: Introductionmentioning
confidence: 97%
“…However, as the SARS-CoV-2 virus undergoes progressive mutations, the global prevalence of the Omicron variant has taken precedence [2]. Notably, recent investigations have shed light on an augmented frequency of seizure incidence in children amidst the ongoing Omicron epidemic [3][4]. In addition, a recent study reported severe neurological disease in several SARS-CoV-2 infected children, with fever and seizures as the main clinical manifestations [5].…”
Section: Introductionmentioning
confidence: 99%